Unlocking the potential of digital finance: a perspective based on the quality of corporate environmental information disclosure - Xinxin Yu; Caihong Yu; Yanjie Zhao; Haosen Peng; Renmiao Yuan; Shuran Feng (Environmental Research Communications)
A pressing issue for both academia and industry is determining how to improve the quality of corporate environmental information disclosure. This study investigates the impact of digital finance on the quality of such disclosure, focusing on non-financial listed companies in China’s Shanghai and Shenzhen A-share markets from 2011 to 2022. The findings are as follows: First, digital finance and its sub-dimensions exert a significant positive influence on disclosure quality, a conclusion validated through a series of robustness checks. Second, a channel mechanism analysis reveals that digital finance enhances disclosure quality primarily by alleviating financing constraints and reducing agency costs, reflecting its effects on resource acquisition and corporate governance. Third, the positive influence of digital finance is more pronounced under weaker environmental regulation and lower public pressure for environmental accountability, suggesting that digital finance functions as an effective complement to existing environmental information supervision. This study contributes to the literature by elucidating the consequences of digital finance for corporate environmental information disclosure and extending the theoretical framework of digital finance in the context of green development.